Pengaruh Struktur Modal, Harga Komoditas, Dan Harga Saham Terhadap Kinerja Keuangan Perusahaan (Studi Empiris Pada Perusahaan Perkebunan Kelapa Sawit Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2022) - Bachtiar Asikin; Wedi Rusmawan Kusumah; Sendi Gusnandar Arnan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the Effect of Capital Structure, Commodity Prices, and Stock Prices on Company Financial Performance (Empirical Study on Palm Oil Plantation Companies Listed on the Indonesia Stock Exchange for the Period 2018-2022). This study uses a quantitative descriptive approach using secondary data obtained from the company's published financial statements. The research population was conducted at oil palm plantation companies listed on the Indonesia Stock Exchange for the period 2018-2022. Based on purposive sampling, a sample of 6 companies was obtained. The results showed that capital structure and commodity prices affect the company's financial performance. While stock prices have no effect on the financial performance of oil palm plantation companies. This study provides further understanding of the factors that can affect the financial performance of oil palm plantation companies in Indonesia. The results of this study can be used as a reference for companies in making decisions related to capital structure, commodity prices, and stock prices. Keywords: Capital Structure, Commodity Price, Stock Price, Corporate Financial Performance